2017
DOI: 10.1128/aem.02967-16
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Secretory Proteins Is Associated with Different Morphotypes in Cryptococcus neoformans

Abstract: Cryptococcus neoformans, an opportunistic human fungal pathogen, can undergo a yeast-to-hypha transition in response to environmental cues. This morphological transition is associated with changes in the expression of cell surface proteins. The Cryptococcus cell surface and secreted protein Cfl1 was the first identified adhesin in the Basidiomycota. Cfl1 has been shown to regulate morphology, biofilm formation, and intercellular communication. Four additional homologs of CFL1 are harbored by the Cryptococcus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…To this end, the α-null mutant was quantitatively or semi-quantitatively examined for its ability to undergo sequential unisexual differentiation processes (Figures S1, and 1D-1H). Our results demonstrated that the removal of α identity genes did not markedly impair unisexual filamentation and the expression level of mCherry-tagged Cfl1 in unisexual communities, which is an indicator protein for filamentous development reported previously (Figure 1D) [35]. Similarly, in the α-null mutant, no detectable defect was identified during basidial maturation, based on the basidial maturation score (BMS) assay that allow us to quantitatively evaluate basidial maturation (Figure 1E) [16].…”
Section: Resultssupporting
confidence: 74%
“…To this end, the α-null mutant was quantitatively or semi-quantitatively examined for its ability to undergo sequential unisexual differentiation processes (Figures S1, and 1D-1H). Our results demonstrated that the removal of α identity genes did not markedly impair unisexual filamentation and the expression level of mCherry-tagged Cfl1 in unisexual communities, which is an indicator protein for filamentous development reported previously (Figure 1D) [35]. Similarly, in the α-null mutant, no detectable defect was identified during basidial maturation, based on the basidial maturation score (BMS) assay that allow us to quantitatively evaluate basidial maturation (Figure 1E) [16].…”
Section: Resultssupporting
confidence: 74%
“…The heterogeneity in the sexual mode in the community might reflect or be enforced by the stochastic expression of Mat2 within the population. Consistent with this idea, we noticed that not all cells responded to the calling of pheromone even under a strong mating-inducing condition [40]. Given that Cryptococcus is a ubiquitous environmental fungus and an opportunistic pathogen to a wide range of hosts, this fungus might have developed various tactics to propagate sexually under different conditions rather than the risky sole dependence on the pheromone pathway and the rare presence of a compatible mating partner.…”
Section: Discussionmentioning
confidence: 80%
“…Cfl1 is a hypha-specific protein downstream of Znf2, and the transcript level of CFL1 correlates with filamentation (6,11,12,43). In the bye1Δ mutant, the transcript level of CFL1 was approximately 16-fold higher than that of the wild type (Fig.…”
Section: Resultsmentioning
confidence: 95%